1998
DOI: 10.1021/jp973264p
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the BrO Self-Reaction:  Temperature- and Pressure-Dependent Studies

Abstract: The flash photolysis/UV absorption technique has been used to study the self-reaction of BrO radicals over the temperature range 222-298 K and the pressure range 100-760 Torr of N 2 or O 2 . Two chemical sources of BrO radicals were used: photolysis of Br 2 in the presence of excess ozone and photolysis of O 2 in the presence of excess Br 2 . The overall rate constant, k 1 , for the BrO self-reaction (defined by -d[BrO]/dt ) 2k 1 [BrO] 2 ) was found to be temperature and pressure independent at T g 250 K, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 29 publications
(108 reference statements)
9
61
3
Order By: Relevance
“…The laboratory measurements were performed using the technique of laser flash photolysis with kinetic UV-visible absorption spectroscopy employing a charged coupled device detection system [Rowley et al, 1996;Harwood et al, 1998]. …”
Section: Experimental Measurementsmentioning
confidence: 99%
“…The laboratory measurements were performed using the technique of laser flash photolysis with kinetic UV-visible absorption spectroscopy employing a charged coupled device detection system [Rowley et al, 1996;Harwood et al, 1998]. …”
Section: Experimental Measurementsmentioning
confidence: 99%
“…This enabled unequivocal determination of BrO concentrations at each time point, despite the presence of other absorbers, as has been demonstrated in our previous work. 33,34,35 The BrO reference spectra were taken from the work of Wilmouth et al 36 These crosssections are reported at higher spectral resolution (0.4 nm FWHM) than spectra recorded in the present study (1.1 nm FWHM), so a smoothing function using a…”
Section: Spectral Analysismentioning
confidence: 82%
“…Signal (photocharge) was transferred row by row down the array, out of the illuminated region, to record sequential wavelength and time resolved transmission spectra of the photolysed mixture on kinetic timescales, as shown, specifically for BrO, in our previous studies. 33,34,35 Spectra were recorded over the wavelength range λ = 274 -338 nm, at a spectral resolution of 1.1. nm full width half maximum. Typically, 1000…”
Section: Radical Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…A photolysis yield of 4% for reaction (I ) was estimated by CRDS measurements for relatively highly concentrated samples (up to 5 × 10 12 molecule cm −3 ) of It should be noted that the concentration of BrO produced is proportional to that of Br 2 only at low concentrations of both Br and BrO. Indeed, for more concentrated samples, the self-reaction of BrO, together with its reaction with bromine atoms, becomes relevant to the kinetics of reaction, leading to BrO depletion [25,26]. Ring-down measurements were taken with the photolysis LEDs off, before and after each series of measurements in order to acquire a reference spectrum, free of BrO.…”
Section: Resultsmentioning
confidence: 99%